Pengaruh Variasi Suhu Terhadap Mutu Abon Ikan Ekonomis Rendah Selama Penyimpanan - Yolanda Cicilia Br. Karo; Rodiana Nopianti; Shanti Dwita Lestari (Jurnal FishtecH, 2017)
The purpose of the research was to know effect of variations temperature on changes in quality of low economic shredded fish during storage. This research used Randomized Block Design (RBD) and Factorial Randomized Block Design (FRBD) with two factors treatments and two replications. The factors were the storage temperatures (40 ºC, 50 ºC, and 60 ºC) and storage time (7, 14, 21, and 28 days). The parameters in this research included chemical and sensory characteristics. The results showed the interaction between storage with storage temperature were significant effect on the water activity, total plate count, total yeast and moulds, appearance, and odor. Based on the analysis of variance (p >0.05) shows that differences storage temperatures (40 ºC, 50 ºC, and 60 ºC) didn’t give significant effect on moisture, fat, protein, and carbohydrate content during 28 days storage while there was significant effect on ash content. Based on sensory test, appearance, odor, flavor, color, and texture scores were range 7; that means the product is still accepted by panelists.